APPLICATION OF THE HOUSE BASED ON TYPE OF HOUSE SPECIFICATIONS USING MICROSOFT VISUAL 6.0 - Bobby Hermawan; Jalinas, SKom, MM Jalinas, SKom, MM (Jurnal Sistem Informasi, 2002)
This application provides specification information about the home form of house type, room specifications, technical specifications, facilities, environment and price list. This application was created to help people who want to get a decent dwelling to be occupied. This application is created using Visual Basic 6.0 pempgraman language with the intention that the resulting display is the user interface.